Peran Pesantren Mahasiswa Internasional Kh. Mas Mansyur Universitas Muhammadiyah Surakarta Dalam Mengader Pendidik Agama Islam Tahun 2016 - Fatimahul Jannah, Mahtsyarul, Dra. Chusniatun, M.Ag (2017)
Islamic boarding school is a place to stay and study for students. One of them is International Islamic Boarding School KH. Mas Mansyur Universitas Muhammadiyah Surakarta which is known as PESMA. PESMA is a place to study and forming of cadres for Regular and International students. One of them is cadres of Islamic teachers. forming of cadres is coachings of PESMA coaches. As for that the role of Islamic boarding school is very important for the future. Based on the background, the aim of this research is to know problem and describe the role that is given by PESMA in forming Islamic cadres. As for the benefit is to give insight as study materials in expanding repertoire of knowledge and giving ideas and thoughts as consideration materials. This research type is field research using descriptive qualitative approach. The methods used are interviewing, observation, and documentation. While the analysis that is used is inductive analysis. As for the source of data in this research is primary data that is obtained from the results of interviewing the director, coaches of Islamic boarding school, and islamic education students and observations on the activities of Islamic education students. The source of secondary data is obtained from collected documents, files, notes, and archives. Based on the data analysis research it can be concluded that the role of International Islamic Boarding School of KH. Mas Mansyur in forming of Islamic cadres is by education and preaching. The role in education covers: training of english, tahsin, and hadits tutors, room coordinator, supporting staff, and teaching staff. The role in preaching covers: short Islamic speech and sermons in foreign languages (English and Arabic) training.